2022
DOI: 10.21037/atm-22-3125
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nutritional status in lung transplant recipients and its correlation with post-transplant short-term prognosis: a retrospective study

Abstract: Background: Lung transplantation is an effective treatment for saving the lives of patients with end-stage lung disease (ESLD). Lung transplant-related morbidity and mortality has significantly higher than other solid organ transplants. Among the pre-transplant variables that affect the survival rate after transplantation, nutritional status are associated with poor survival rate. In order to provide basis for formulating nutritional evaluations for lung transplant recipients in the future, we retrospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…55,57 Altered gastrointestinal conditions such as gastroesophageal reflux disease, dysphagia, ineffective esophagus, gastroparesis, and restrictive scleroderma also exacerbate the risk for malnutrition. 4,[57][58] Severe malnutrition, low BMI, and gastrointestinal conditions that increase the risk for reflux, aspiration, and rejection may require prolonged periods of nothing by month (NPO)…”
Section: End-stage Lung Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…55,57 Altered gastrointestinal conditions such as gastroesophageal reflux disease, dysphagia, ineffective esophagus, gastroparesis, and restrictive scleroderma also exacerbate the risk for malnutrition. 4,[57][58] Severe malnutrition, low BMI, and gastrointestinal conditions that increase the risk for reflux, aspiration, and rejection may require prolonged periods of nothing by month (NPO)…”
Section: End-stage Lung Diseasementioning
confidence: 99%
“…Results from a 2022 study indicated that patients with high nutrition risk had significantly increased post-op chest tube drainage 24-h post-transplant, significantly increased ICU LOS, and significantly higher hospital costs (p < .05). 4 A 2020 study found that non-CF patients with high malnutrition risk were more likely to have low BMI and shorter 6-min walk distance. There was no association with ICU admission in the pre-transplant period, delisting, or mortality.…”
Section: End-stage Lung Diseasementioning
confidence: 99%
See 3 more Smart Citations